Harmonious, Dynamic, and Equitable Industrial Relations Dispute Resolution in The Eyelash Industry in Purbalingga - Wardani, Susilo; Dwiyanti, Retno; Supriyanto, Agustinus (Jurnal Dinamika Hukum, 2022)
Purbalingga Regency is one of the centers of eyelash production in Indonesia. Thousands of people work in this sector. However, the Covid-19 pandemic has increased industrial relations disputes that arise because of differences in interests between employers and workers/laborers. This article aims to unravel industrial relations disputes in the eyelash industry and formulate a harmonious, dynamic, and equitable settlement model. This research is designed using empirical juridical method. Data analysis for centralized research is carried out by systematizing legal materials obtained and classified while field research is classified and tabulated based on answers to questions in the interview guidelines. The results show that the settlement of industrial relations disputes that are harmonious, dynamic, and fair in the false eyelash industry sector in Purbalingga Regency is resolved through bipartite institutions. If it fails, mediation is conducted. In resolving industrial relations disputes, it is necessary to get rid of the concept of balance of power or opposition.Keywords: Dispute Resolution, Industrial Relations, Harmony, and Justice.